Interpretation of the Results of Geo-electric Sounding Based on a Mathematical Model of Double-layered Soil - Grbić, Maja; Salamon, Dragutin; Pavlović, Aleksandar (Proceedings, Electrical engineering institute "Nikola Tesla", 2013)
This paper presents the soil resistivity testing results carried out at the location designated for the construction of substation 110/35/10 kV Zlatibor. Testing results show that the tested soil is double-layered. Interpretation of the results of geo-electric sounding based on a mathematical model of double-layered soil shows good matching with the test results.